Configuring System Internetwork Operating System (IOS) Cisco At Wide Area Network Using the Frame Relay Router Simulator Network Visualizer version 4.0. - Rorim Irvano Prahara; Melani D L, SKom, MMSI (Jurnal Sistem Informasi, 2006)
Scientific writing is about how to configure Cisco IOS software (Internetwork Operating System) which is owned by Cisco routers in the network system Wide Area Network (WAN). In writing this scholarly study authors about how to connect the companies or institutions that have branches or associates that were located far from the logic of using frame relay technology which provides additional functionality for dynamic bandwidth allocation, congestion control is also cost-efficient which can provide networking solutions to the company or agencies that are still using dial-up facility with analog modems Cisco router configuration system on the network Wide Area Network (WAN) is created using the software simulator program Network Visualizer is a software clone of the Internetwork Operating System (IOS) which is in Cisco's router system.